Radiofrequency Ablation: Mechanism of Action and Devices - Hong, Kelvin; Georgiades, Christos (Journal of vascular and interventional radiology, 2010)
Since the first radiofrequency (RF) ablation description in early 1990's for percutaneous tumor ablation, there has been considerable published data on the subject worldwide. An understanding of RF ablation equipment, mechanism of action and its interactions with tissue is critical to avoid complications and improve patient outcomes. There is considerable variability in the way that RF ablation may be performed, and there is a variety of equipment choices. Despite the accumulated data, the desire to more quickly obtain larger zones of ablation has quickly spurred the introduction of several new ablation modalities. However, RF ablation remains the prototypical thermal ablation technique.